Delayed Diagnosis of Infected Posterior Mediastinal Teratoma - Reddy, KR Bharath Kumar (EL-MED-Pub, 2013)
Mediastinal teratomas are rarely reported in children. We report a 12-year-old child, diagnosed and treated as empyema thoracis in a peripheral setting for 18 months. In our centre, CT scan performed revealed a well circumscribed multiloculated cystic lesion containing fat, bone and teeth, suggestive of a teratoma. The mass was excised and found to be an infected posterior mediastinal teratoma, confirmed on histopathology.